Successes and challenges of the APP Coronagraph. Issue Volume 8:Issue S299(2013) (6th January 2014) - Kenworthy, Matthew A.; Quanz, Sascha; Otten, Gilles; Meshkat, Tiffany; Codona, Johanan; Snik, Frans; Meyer, Michael E.; Kasper, Markus; Girard, Julien
Abstract: The Apodizing Phase Plate (APP) coronagraph has been used to image the exoplanet β Pictoris b and the protoplanet candidate around HD 100546, and is currently in use in surveys with NaCo at the VLT. Its success is due to its tolerance to tip-tilt pointing errors in current AO systems, which degrade the performance of nearly all other coronagraphs. Currently the sensitivity of the APP is limited by non-common path errors in the science camera systems and by its chromatic behaviour. We present the achromatized Vector APP coronagraph and address how we will measure and minimise non-common path errors with Focal Plane Wavefront Sensing algorithms.